1969
DOI: 10.1099/00221287-58-1-125
|View full text |Cite
|
Sign up to set email alerts
|

Linear Growth Kinetics of Plaque-forming Streptococci in the Presence of Sucrose

Abstract: Growth of intact plaques of dextran-forming strain SL-I was linear both on a dry weight and DNA basis. Growth of broth cultures of dextran-forming strains SL-I and E-49 was linear with sucrose but exponential with other sugars; non dextran-forming strains 4M4 and JR8LG grew exponentially with all sugars tested. When dextranase was added to slowly growing cultures of dextran-forming strains SL-I and E-49, growth became rapid. Linear growth of strains SL-I and E-49 with sucrose is ascribable to extracellular dex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

1969
1969
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 16 publications
1
19
1
Order By: Relevance
“…Polysaccharide levels were highest at lower dilution rates, as were the mean residence times of the organism, but decreased with increasing dilution rate, although the cell population remained constant. At the lower dilution rates the higher polysaccharide levels may themselves be growth limiting, as Tanzer et al (1969) reported that growth restriction of plaque-forming streptococci was associated with dextran formation, whilst Moraine & Rogovin (1973) proposed that increased fermentation viscosities and encapsulation were factors which contributed to growth limitation by restricting the transport of nutrients into the cell. However, in this series of experiments, fermentation conditions were pre-selected so that, in general, the polysaccharide content, and hence viscosity, of the fermentation liquor was such that efficient aeration of the culture was possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polysaccharide levels were highest at lower dilution rates, as were the mean residence times of the organism, but decreased with increasing dilution rate, although the cell population remained constant. At the lower dilution rates the higher polysaccharide levels may themselves be growth limiting, as Tanzer et al (1969) reported that growth restriction of plaque-forming streptococci was associated with dextran formation, whilst Moraine & Rogovin (1973) proposed that increased fermentation viscosities and encapsulation were factors which contributed to growth limitation by restricting the transport of nutrients into the cell. However, in this series of experiments, fermentation conditions were pre-selected so that, in general, the polysaccharide content, and hence viscosity, of the fermentation liquor was such that efficient aeration of the culture was possible.…”
Section: Discussionmentioning
confidence: 99%
“…The observed pattern suggested that at higher input levels factors other than the nitrogen content were growth limiting. Culture viscosity and encapsulation have been implicated in restricted nutrient transport into the cell with resultant growth limitation (Tanzer, Wood & Krichevsky, 1969;Moraine & Rogovin, 1973).…”
Section: Efsect Of Medium Composition On Steady-state Exopolysaccharimentioning
confidence: 99%
“…This assumption of slow streptococcal multiplication in plaque in vivo is indirectly supported by the calculations of G ibbo ns [1964a], the data of G ibbo ns and Kapsimalis [1967], and by the common observation that adhesive plaques in vivo do not increase in extent many fold per day. Furthermore, recent studies have shown that even in the presence of com plex bacterial growth medium containing sucrose, plaque-forming strepto cocci are incapable of rapid growth [Tanzer et al, 1969]. Thus, plaque on the surface of the tooth probably functions, at least most of the time, Preparation of suspensions.…”
Section: Introductionmentioning
confidence: 99%
“…Because supragingival plaque adheres to tooth surfaces and is not bathed in either blood or interstitial fluids, topical antiseptic agents would appear to be of greatest utility. In addition, dental plaque is representative of a slow-growing microbial system (27,31). Therefore, for an agent to be efficacious, it must be able to permeate the plaque matrix and rapidly kill at least the pathogenic members of the plaque microflora after only transient exposures.…”
mentioning
confidence: 99%